Decadal climate variability in the Argentine Pampas: regional impacts of plausible climate scenarios on agricultural systems - Podestá, Guillermo (2009)
The Pampas of Argentina have shown some of the most consistently increasing trends in precipitation during the 20th century. The rainfall increase has partly contributed to a significant expansion of agricultural area, particularly in climatically marginal regions of the Pampas. However, it is unclear if current agricultural production systems, which evolved partly in response to enhanced climate conditions, may remain viable if (as entirely possible) climate reverts to a drier epoch. We assess the potential impacts of a plausible decreasing trend in precipitation on the economic sustainability of 2 contrasting agricultural systems in the Pampas: Pergamino, in the most productive subregion of the Pampas, and Pilar, in the northern, semi-arid margin of the region. Also, we explore the scope for adaptation to changing climate. In the case where there is no adaptation, if precipitation decreases, as is plausible, impacts may be quite different between locations: whereas in Pergamino crop economic returns would not change noticeably, the more marginal Pilar would experience a marked decrease in profits and an increase in production risks. However, potential negative impacts might be mitigated, in part, if farmers adapt their agronomic management using current available technology or know-how.